2018
DOI: 10.1016/j.yhbeh.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Women's preferences for men's beards show no relation to their ovarian cycle phase and sex hormone levels

Abstract: According to the ovulatory shift hypothesis, women's mate preferences for male morphology indicative of competitive ability, social dominance, and/or underlying health are strongest at the peri-ovulatory phase of the menstrual cycle. However, recent meta-analyses are divided on the robustness of such effects and the validity of the often-used indirect estimates of fertility and ovulation has been called into question in methodological studies. In the current study, we test whether women's preferences for men's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 108 publications
(132 reference statements)
0
20
1
Order By: Relevance
“…During the menstrual cycle, women's preferences for masculinity in male faces, voices and behavior are subjected to changes which are the strongest in periovulatory period (9). On the other hand, recent studies showed that women's preferences for men's facial masculinity did not change over the menstrual cycle and were not associated with levels of estradiol, progesterone or luteinizing hormone (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the menstrual cycle, women's preferences for masculinity in male faces, voices and behavior are subjected to changes which are the strongest in periovulatory period (9). On the other hand, recent studies showed that women's preferences for men's facial masculinity did not change over the menstrual cycle and were not associated with levels of estradiol, progesterone or luteinizing hormone (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Higher estradiol level correlated with a preference for androgen-dependent traits in men (13). On the other hand, recent studies showed that women's preferences for men's facial masculinity did not change over the menstrual cycle and were not associated with levels of estradiol, progesterone or luteinizing hormone (14,15). Interestingly, based on the assessment of photographs, single men's faces were rated by women as more masculine and thus more attractive than those of partnered men (16).…”
Section: Introductionmentioning
confidence: 89%
“…These studies have reported mixed results, potentially because they were generally particularly badly underpowered [34] and/or because the substantial genetic variation in mate preferences [39] There has recently been a concerted effort by many researchers to address these potentially important methodological limitations. For example, several recent large-scale, within-subject studies have investigated women's preferences for facial masculinity [40][41][42], beardedness [42,43], body masculinity [41,44], facial symmetry [41], or vocal masculinity [45] using luteinizing hormone (LH) tests and/or other hormone measures to confirm the timing and occurrence of ovulation. Notably, none of these studies observed significant effects of fertility on women's preferences for masculine or symmetric men.…”
Section: Methodological Problems With Previous Researchmentioning
confidence: 99%
“…The clean-shaven and bearded photographs were used to construct composite stimuli using the Webmorph software package (DeBruine & Tiddeman, 2016). 189 facial landmarks were identified on each image, and composite images were created by randomly selecting five of the thirty-seven individuals and averaging shape and color information of the clean-shaven images, as well as the corresponding bearded versions of the same individuals (Dixson et al, 2018;McIntosh et al, 2017). For an example of the stimuli see Figure 1.…”
Section: Facial Compositesmentioning
confidence: 99%